The Ingroup–Outgroup Relationship Influences Their Humanity: A Moderation Analysis of Status and Gender - Arriagada-Venegas, Matías; Pérez-Jorge, David; Ariño-Mateo, Eva (Frontiers in Psychology, 2021)
The present study aimed to examine whether gender and status moderate the teacher-student relationship and the perception of dehumanization in professors and students. 528 participants from a university in Laguna (74% students and 26% professors) completed a questionnaire based on the teacher-student relationship scale, organizational dehumanization, and demographic variables. The software utilized to analyze the data was PROCESS, a mediation and moderation package. The results indicated that ingroup-outgroup relationship influences the perception of organizational dehumanization significantly (p <.001). Furthermore gender (p <.001) and status (p <.001) have moderating roles, specifically female students are at most risk of perceiving themselves dehumanized and males with high status (teachers) less vulnerable of dehumanization. These findings are very significant for the advancement in the knowledge of the intergroup relationship and organizational dehumanization and have practical implications for teachers and students.